Molecular distillation and characterization of diacylglycerol-enriched palm olein - Yeoh, Chiou Moi; Phuah, Eng Tong; Tang, Teck Kim; Siew, Wai Lin; Abdullah, Luqman Chuah; Choong, Thomas Shean Yaw (Wiley, 2014)
Lipase-catalyzed glycerolysis of palm olein was used to produce a mixture of acylglycerols with ∼34-wt% of DAG. The reaction conditions were 5-wt% of Lipozyme TLIM at 55°C and 8 h of reaction time. For commercial purposes, it is required to purify the product up to 80-wt% DAG and with free fatty acids (FFA) content below 0.1-wt%. A single-step distillation process was not sufficient to meet this product requirement. Two distinct 2-step short path distillation approaches were then studied. First scheme involved the removal of TAG by initial distillation step at 250°C, followed by separation of the MAG and FFA from distillate obtained at 180°C during second distillation step at vacuum pressure of 0.1 Pa. Second scheme involved the removal of MAG and FFA in first step at 180°C prior to purification of DAG from residue at 250°C during second distillation step at vacuum achieved up to 0.1 Pa. The results suggested that the first scheme of 2-step distillation operation was able to achieve 89.9-wt% of DAG purity without exceeding the limit of 0.1-wt% of FFA. A final yield of 21.5-wt% and DAG recovery of 47.8% were obtained using the first scheme. A detailed DAG profile was identified and product characterizations such as fatty acid composition, slip melting point, and solid fat content profile were also investigated. It was observed that purified-DAG product showed lower iodine value and higher slip melting point than raw material palm olein. The final product had 1134 ± 10 ppm tocols content.